DEVELOPING LEARN TENSES FOR STUDENTS’ GRAMMATICAL MASTERY IN SENIOR HIGH SCHOOL - Rahmaddian, Aldy; Fakhrurriana, Ria (ELite Journal : International Journal of Education, Language and Literature, 2023)
Learning grammar is important for beginners. Having a basic awareness and command of grammar in writing is of vital importance. But, learning grammar can be challenging for beginners. According to a survey of over 1,000 teachers, the biggest grammar challenges for English language learners include difficulty remembering grammar rules, difficulty understanding complex grammar concepts, and difficulty applying grammar rules in context. Mobile learning enables learners to utilize any equipment and technology they possess, in any place, at any time, providing them with opportunities to enhance their learning experiences. The main objective of this study was to develop a smartphone application in the form of an APK (Android Package Kit) specifically designed for their English learning. The research methodology employed in this study is Research and Development (R&D). The product, in this case, was the Learn Tenses learning materials, which were developed in response to field demands. To create the learning assistant, the researcher utilized the Construct 4 application. The games aim to increase the grammar mastery of all-grade students of senior high school. It can be played using a smartphone and other Android-based. Based on the three validation results that the android-based game created in this study is suitable for implementation, achieving a score of 86%.